La ética civil en Colombia - Vélez Vélez, Marco Antonio (La Sociología en sus Escenarios, 2009)
Abstract The Colombian citizen of today appears to be affected by a shortfall corporate and civility, making it difficult coexistence. This has convened since the urgency of filling reflection, Political and policy at the same time, many expressions of this absence. There is no clarity yet on the nature of a possible maximum of ethics, to redirect the course of the civil society action. The basis for building such peak thinks differently. The options range from a possible reconstruction of a religious basis to the highest ethical, up possibilities that arise from a secular thought and reflection on, tica. This line of thought to, Political citizen today, which is intended to pick up this paper. The construction of this proposal, Political, secular and civilian at the same time, for the contemporary Colombia, addressed progressively, from the issues of the ethical principles that underlie, Political civilian possible to reconfigure the highest ethical deficit of civility among us today. A "culture of maximum" to guide normatively the subjects, is not perhaps a demand for a smaller, Political civil and secular. Resumen El ciudadano colombiano de hoy parece estar afectado de un déficit societario y de civilidad, que hacen difícil la convivencia. Esto ha convocado la urgencia de colmar desde la reflexión ‚tica y política a la vez, las expresiones múltiples de esta ausencia. No hay claridad sin embargo, sobre la naturaleza de unas posibles máximas éticas, para reorientar los cursos de la acción civil y social. El fundamento de construcción de dichas máximas se piensa diversamente. Las opciones van desde, una posible reconstrucción de un fundamento religioso para las máximas éticas, hasta posibilidades que surgen de un pensamiento y reflexión secular sobre la ética. Esta última línea de reflexión para la ‚tica ciudadana de hoy, es la que pretende recoger el presente trabajo. La construcción de esta propuesta ‚tica, secular y civil a la vez, para la Colombia contemporánea, abordar progresivamente, desde las cuestiones de principios éticos que fundamentan la ‚tica civil posible, hasta máximas éticas que reconfiguran el déficit de civilidad presente entre nosotros hoy. Una "cultura de máximas", que guíen normativamente a los sujetos, no es quizás, una exigencia menor para una ‚tica civil y secular